2001
DOI: 10.4269/ajtmh.2001.65.143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of vivax malaria.

Abstract: Abstract. Plasmodium vivax malaria reemerged in the Republic of Korea in 1993 near the Demilitarized Zone (DMZ). We reviewed clinical features of 101 symptomatic patients with vivax malaria. Of the patients, 77 patients (76.3%) were veterans who had served near the DMZ; their median age was 23 years. The duration of the minimum latent period was Ͼ 6 months in 66.2% (51 of 77) of the patients (median, 278 days). Tertian fever developed in 69 patients (68.3%). Severe thrombocytopenia with platelet counts Ͻ 60,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
4
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 11 publications
9
55
4
1
Order By: Relevance
“…Similar to the current study, lymphopenia has also been reported in falciparum patients from other geographic locations (28). Depletion in the lymphocyte subsets through apoptosis (29) or due to sequestration of the cells in the lymph nodes or other body tissues (30) are some of the reasons behind the occurrence of lymphopoenia in malaria patients.…”
Section: Discussionsupporting
confidence: 72%
“…Similar to the current study, lymphopenia has also been reported in falciparum patients from other geographic locations (28). Depletion in the lymphocyte subsets through apoptosis (29) or due to sequestration of the cells in the lymph nodes or other body tissues (30) are some of the reasons behind the occurrence of lymphopoenia in malaria patients.…”
Section: Discussionsupporting
confidence: 72%
“…However, even if this statement is true for these regions, atypical manifestations denoting severity have been observed in an increasing way 6,8,15 . Signs and symptoms, such as vomiting, diarrhea, jaundice, drowsiness, mental confusion, seizures, loss of consciousness, bleeding, and dyspnea, that registered in a significant percentage of patients confirm these findings.…”
Section: Rev Soc Bras Med Trop 46(1):67-72 Jan-feb 2013mentioning
confidence: 94%
“…Geralmente a gravidade dos casos de malária está 30,31 associada à demora do diagnóstico e do tratamento , porém, como em zonas epidêmicas ou endêmicas da doença no Brasil as pessoas estão atentas aos sintomas da malária, buscando normalmente atendimento logo no início das manifestações clínicas, isso torna infrequente os quadros graves. Como cerca de 22% dos pacientes procurou atendimento com menos de 48 h; mais de 70% das pessoas incluídas nessa amostra procuraram atendimento com menos de quatro dias a partir do início dos sintomas; e a maioria dos pacientes cursava com malária pelo P. vivax, provavelmente essas são as explicações para o encontro apenas de casos não graves nessa casuística.…”
Section: Materiais E Métodosunclassified